Centro comercial avenida: um espaço aberto à cidade - Ramos, Henrique Sérgio Macedo (2016)
This dissertation presents the research and design stages for an architectural project of a commercial building, comprising both retail and offices, whose configuration fosters its relationship with the public realm. Its approach focuses on the attributes of urbanity – a concept intrinsically related to urban vitality and the recognition of the other in the city space. The research is justified by the perception that the design of many commercial buildings of our cities promotes the disconnection between public and private spaces, having a negative impact not only in the economic activities of the commercial development, but also potentially leading to the emptiness of the urban environment. Based on the space syntax theoretical approach, this paper argues that the built form, as well as the urban configuration, exerts effects on patterns of urbanity, urban vitality and co-presence - key concepts to be explored in this dissertation. To assist in the development of the architectural proposal, a review of the literature on both direct and indirect references related to the key concepts was carried out, followed by an identification of such attributes in building complexes of similar use to the object of study, leading to the application of these concepts to the design. Space syntax tools were also applied in the research process in order to simulate accessibility and visibility properties that associate such concepts and ground the design proposal. The universe of study is an urban lot located in the Lagoa Nova neighborhood, Natal-RN.